Predictors of functional impairment in bipolar disorder: Results from 13 cohorts from seven countries by the global bipolar cohort collaborative. (15th April 2022) - Burdick, Katherine E.; Millett, Caitlin E.; Yocum, Anastasia K.; Altimus, Cara M.; Andreassen, Ole A.; Aubin, Valerie; Belzeaux, Raoul; Berk, Michael; Biernacka, Joanna M.; Blumberg, Hilary P.; Cleare, Anthony J.; Diaz‐Byrd, Claudia; et al.
Abstract: Objectives: Persistent functional impairment is common in bipolar disorder (BD) and is influenced by a number of demographic, clinical, and cognitive features. The goal of this project was to estimate and compare the influence of key factors on community function in multiple cohorts of well‐characterized samples of individuals with BD. Methods: Thirteen cohorts from 7 countries included n = 5882 individuals with BD across multiple sites. The statistical approach consisted of a systematic uniform application of analyses across sites. Each site performed a logistic regression analysis with empirically derived "higher versus lower function" as the dependent variable and selected clinical and demographic variables as predictors. Results: We found high rates of functional impairment, ranging from 41 to 75%. Lower community functioning was associated with depressive symptoms in 10 of 12 of the cohorts that included this variable in the analysis. Lower levels of education, a greater number of prior mood episodes, the presence of a comorbid substance use disorder, and a greater total number of psychotropic medications were also associated with low functioning. Conclusions: The bipolar clinical research community is poised to work together to characterize the multi‐dimensional contributors to impairment and address the barriers that impede patients' complete recovery. We must also identify the core features which enable many to thrive and live successfully with BD. A large‐scale, worldwide, prospective longitudinal study focused squarely on BD and its heterogeneous presentations will serve as a platform for discovery and promote major advances toward optimizing outcomes for every individual with this illness.